Perspektif Mahasiswa Ilmu Administrasi Negara mengenai Efektivitas Demonstrasi - Putra, Zaki Anandya; Saputry, Andhrea Haning; Rahayu, Mifta Khoirul Putri; Septiyani, Kiki Imas; Shodiqin, Ichsan; Nugraha, Joko Tri (Jurnal Politik dan Pemerintahan Daerah, 2025)
This research aims to identify the perceptions of Public Administration students regarding the effectiveness of demonstrations and to explore more relevant alternative forms of public participation. Using a descriptive quantitative approach, the research employed an online survey with 75 respondents, whose data were analyzed through frequency distributions, mean values, standard deviations, and thematic qualitative analysis of open-ended responses. The results indicate that while many students still view demonstrations as an effective way to convey aspirations, a significant number prefer social media as a strategic mobilization tool. Social media is considered capable of reaching a broader audience with lower risk compared to physical demonstrations. Additionally, alternatives such as online petitions and formal audiences have emerged as relevant and strategic options. Respondents believe that digital participation is more inclusive and accessible, enabling greater involvement in the advocacy process. Nonetheless, demonstrations retain an important symbolic role as a visible form of public pressure on policymakers. In conclusion, students are beginning to shift their political participation paradigm from traditional methods like demonstrations toward more modern, safe, and efficient strategies based on digital technology. This shift reflects an adaptation to evolving social and technological dynamics, whereby students leverage both field actions and the vast potential of digital spaces to convey aspirations and influence public policy effectively.